2000
DOI: 10.1128/iai.68.7.4217-4224.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Most Abundant Glycoprotein of Amebic Cyst Walls (Jacob) Is a Lectin with Five Cys-Rich, Chitin-Binding Domains

Abstract: The infectious stage of amebae is the chitin-walled cyst, which is resistant to stomach acids. In this study an extraordinarily abundant, encystation-specific glycoprotein (Jacob) was identified on two-dimensional protein gels of cyst walls purified from Entamoeba invadens. Jacob, which was acidic and had an apparent molecular mass of ϳ100 kDa, contained sugars that bound to concanavalin A and ricin. The jacob gene encoded a 45-kDa protein with a ladder-like series of five Cys-rich domains. These Cys-rich doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 52 publications
3
101
0
Order By: Relevance
“…Such staining is consistent with processing of the EhNucI-HA and EhNucII-HA proteins through the rudimentary endoplasmic reticulum present in these parasites for entry into the secretory system. Importantly, very similar immunofluorescence staining patterns have been reported for other secretory proteins in these parasites (44,45). In contrast to the above, no fluorescence was detected in cells transfected with the ExEhNeo control plasmid (data not shown).…”
Section: -180 Min)supporting
confidence: 48%
“…Such staining is consistent with processing of the EhNucI-HA and EhNucII-HA proteins through the rudimentary endoplasmic reticulum present in these parasites for entry into the secretory system. Importantly, very similar immunofluorescence staining patterns have been reported for other secretory proteins in these parasites (44,45). In contrast to the above, no fluorescence was detected in cells transfected with the ExEhNeo control plasmid (data not shown).…”
Section: -180 Min)supporting
confidence: 48%
“…2E) (24). Similarly, the walls of Saccharomyces and the sheath of nematodes are a single layer of uniform thickness and staining.…”
Section: First Strategy: Assume That At Least Some Of the Important Cmentioning
confidence: 99%
“…In turn, FITC-lectin avidity of Acanthamoeba and Naegleria strains differed between morphological forms, species and pathogenic or nonpathogenic strains of the same species (Bose et al 1989). More sophisticated Entamoeba studies have not only demonstrated further the experimental potential of fluorescent lectins in elucidating protozoan cell surface nature and dynamics (Ribeiro et al 1997), but also the natural role of lectins as encystation-specific glycoproteins in cyst-wall maturation (Frisardi et al 2000). The studies outlined below employ the techniques of flow cytometry and a panel of FITC-lectins and concepts developed from ligand-receptor studies, to characterize Acanthamoeba polyphaga cyst and trophozoite lectin avidity, hence surface carbohydrate nature.…”
Section: Introductionmentioning
confidence: 99%